Design and Analysis of UI Effectiveness for SDGs Interactive Learning Media Using Heuristic Evaluation - Deli; Suwarno; Joanntika Lewis; Risna Yunita (Applied Information System and Management (AISM), 2026)
Interactive learning media must be capable of presenting the concept of Sustainable Development Goals (SDGs) in an engaging and easily understandable way for students in support of achieving the Sustainable Development Goals. However, the effectiveness of such media is strongly influenced by user interface (UI) quality, as poor UI design can cause confusion, reduce user engagement, and hinder users' understanding of SDG concepts. This research aims to develop and analyze interactive learning media that support the dissemination of SDG content. The Multimedia Development Life Cycle (MDLC) method was used to develop the interactive learning medium, and the user interface was analyzed using the heuristic evaluation method, with questionnaires distributed to 200 high school students. The results show that the developed interactive learning medium achieved a "High" level of UI effectiveness with an average score of 4.04. The aesthetic and minimalist design principle (HE08) was the indicator that scored highest, indicating that respondents considered the system's visual design well implemented, ensuring users felt comfortable and did not encounter significant usability issues. The principles of error prevention (HE05) and helping users recognize, diagnose, and recover from errors (HE09) received lower scores, highlighting areas that require improvement. Overall, studies have demonstrated that the interactive learning medium improves student engagement and the learning experience with respect to SDG concepts. This research contributes to the development of interactive learning media and guides future research on interface improvement.